An automated method for DNA preparation from thousands of YAC clones. - MacMurray, A J (1991)
We describe an automated method for the preparation of yeast genomic DNA capable of preparing thousands of DNAs in parallel from a YAC library. Briefly, the protocol involves four steps: (1) Yeast clones are grown in the wells of 96-well microtiter plates with filter (rather than plastic) well-bottoms, which are embedded in solid growth media; (2) These yeast cultures are resuspended and their concentrations determined by optical density measurement; (3) Equal numbers of cells from each well are embedded in low-melting temperature agarose blocks in fresh 96-well plates, again with filter bottoms; and (4) DNA is prepared in the agarose blocks by a protocol similar to that used for preparing DNA for pulsed-field gels, with the reagents being dialyzed through the (filter) bottoms of the microtiter plate. The DNA produced by this method is suitable for pulsed-field gel electrophoresis, for restriction enzyme digestion, and for the polymerase chain reaction (PCR). Using this protocol, we produced 3000 YAC strain DNAs in three weeks. This automated procedure should be extremely useful in many genomic mapping projects.